Fathers’ perceptions of factors associated with the attainment of paternity leave: a qualitative study - Mita, Naoyuki; Khin, Yu Par; Nawa, Nobutoshi; Yamaoka, Yui; Fujiwara, Takeo (Frontiers in Global Women's Health, 2025)
BackgroundA systematic review has reported that paternal involvement is beneficial in reducing social, behavioural and psychological problems in children. However, little research has investigated factors associated with the attainment of paternity leave.ObjectiveThe objective of this study was to explore fathers’ perceptions of the factors associated with taking paternity leave.Participants and settingOverall, 21 in-depth interviews were conducted with fathers to obtain information on their perceptions of paternity leave. We also conducted key informant interviews with four supervisors at companies to understand their opinions on paternity leaves and ensure that the implications of this study are relevant at workplaces.MethodsThematic analysis was adopted to analyse the data. Deductive coding was conducted based on previous studies on paternity leave, followed by inductive coding and modification of the initial codes. The final codes were organised based on the social-ecological model.ResultsThemes associated with taking paternity leave included fathers’ career aspirations, fathers’ commitment to supporting infants or mothers, mothers’ or infants’ need for fathers’ involvement, colleagues’ outlook on paternity leaves, fathers’ work schedules or responsibilities, support from relatives, paternity leave policies, and trends toward fathers’ involvement. The supervisors mentioned themes related to paternity leave from the broader perspective of long-term effects and impact on the organisation.ConclusionsThis study revealed fathers’ perceptions regarding the factors associated with taking paternity leave. The results may provide useful information on how to create an environment in which fathers can easily take paternity leave.